2017
DOI: 10.3390/en10122057
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis and Evaluation of the Numerical Prediction of Wake Characteristics of Tidal Stream Turbine

Abstract: Abstract:It is important to understand tidal stream turbine performance and flow field, if tidal energy is to advance. The operating condition of a tidal stream turbine with a supporting structure has a significant impact on its performance and wake recovery. The aim of this work is to provide an understanding of turbine submerged depth that governs the downstream wake structure and its recovery to the free-stream velocity profile. An experimentally validated numerical model, based on a computational fluid dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Moreover, the turbine closeness to the water surface promoted the flow modification around the turbine which affected the wake development downstream the rotor. Finally, supported by the presented results, Zhang et al [16] claimed that CFD is an appropriate tool to simulate the performance of tidal turbines and that the turbine proximity to the water surface influences the wake recovery.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, the turbine closeness to the water surface promoted the flow modification around the turbine which affected the wake development downstream the rotor. Finally, supported by the presented results, Zhang et al [16] claimed that CFD is an appropriate tool to simulate the performance of tidal turbines and that the turbine proximity to the water surface influences the wake recovery.…”
Section: Introductionsupporting
confidence: 66%
“…When comparing with experimental data, Reference [15] found that both models captured reasonably well the wake dynamics, although there was around a 5% difference between both predictions. Reference [16] presented comparisons between experiments and CFD numerical computations focused on the velocity profiles in the wake region of a HAHT. The agreement between them was very reasonable, showing the same predicted wake recovery trend.…”
Section: Introductionmentioning
confidence: 99%
“…ICEM CFD software was used to obtain the mesh of the computing domain [14]. e unstructured grids were adopted due to its strength in the adaptability of the complicated and irregular geometry.…”
Section: Boundary Condition and Mesh Refinement Studymentioning
confidence: 99%
“…Although several approaches exist for the purpose of multiobjective optimization design of the pumps and impellers, programs using computational uid dynamics (CFD) continues to be the most popular method [10][11][12]. ese programs, when run by high-performance computers, can forecast not only the functioning of the pump but also the ow eld upstream and downstream of the pump [13][14][15]. For instance, Zhang et al [16] validated a CFD model, used for optimizing the submerged propeller operated in an oxidation ditch.…”
Section: Introductionmentioning
confidence: 99%
“…e transient process model of pumped storage unit was solved by using the method of characteristics, and the basic motion and continuity equation of unsteady flow in pressurized pipeline are shown below [28][29][30][31][32].…”
Section: Methods Of Characteristicsmentioning
confidence: 99%